Upaya Meningkatkan Konsentrasi Anak Pada Usia 4-5 Tahun Melalui Media Loose Parts Di PAUDQ Al-Fitrah Pondok Melati Kota Bekasi - Maulidya , Fildza; AE, Yon; Kurniawaty , Lia (CV. ITTC INDONESIA, 2024)
Children's concentration is still a problem that needs to be overcome, the concentration span is relatively less than 2 minutes, which has an impact on their overall learning process. This research was carried out at PAUDQ Al-Fitrah and focused on group A aged 4-5 years. The scope of this research was to analyze the application of loose part media for the concentration of children aged 4-5 years. It is hoped that it can provide an effective solution in increasing the concentration of children aged 4-5 years. year. Researchers used classroom action research, and used the Kemmis and Mc Taggart research methods. The data collection techniques used were observation, interviews and documentation. One of the criteria for the success of the action expected in this research is an increase in the concentration of children aged 4-5 years at PAUDQ Al-Fitrah. The research results show an increase in the observation sheets and graphs in chapter IV. The results of research cycles I and II showed an increase in the percentage for each child. In conclusion, the use of loose parts media has proven to be an effective strategy in increasing the concentration of children aged 4-5 years at PAUDQ Al-Fitrah Pondok Melati, Bekasi City